Intercultural Discipleship : Learning from global approaches to spiritual formation - Moon, W. Jay (Encountering Mission, 2017)
This addition to an acclaimed series brings cutting-edge research to bear on a topic of perennial interest: making disciples. The book looks at disciple-making from multiple cultures to help readers discover contextual approaches that are culturally relevant and biblically faithful. It emphasizes methods that are especially effective with contemporary converts and includes practical examples from around the world. Each chapter includes sidebars, discussion questions, an activity for discipling, and a case study. An appendix contains further suggestions and exercises for instructors.